2016
DOI: 10.1089/neu.2014.3786
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hormonal Imbalance and Adipose Redistribution Is Associated with Hypothalamic Neuropathology following Blast Exposure

Abstract: Endocrine disorders have been shown to be a consequence of blast traumatic brain injury in soldiers returning from military conflicts. Hormone deficiency and adrenocorticotropic hormone (ACTH) dysfunction can lead to symptoms such as fatigue, anxiety, irritability, insomnia, sexual dysfunction, and decreased quality of life. Given these changes following blast exposure, the current study focused on investigating chronic pathology within the hypothalamus following blast, in addition to systemic effects. An esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Numerous pathological outcomes have been identified in relation to BINT. Neurochemical alterations/imbalance, oxidative stress, mitochondrial dysfunction and BBB disruption have been identified to be important pathological events that are involved at acute stages following BINT 3 4 5 6 7 8 9 10 11 12 13 14 15 21 22 23 . However, the long-term effects on various pathological markers and associated cognitive deficits are currently unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous pathological outcomes have been identified in relation to BINT. Neurochemical alterations/imbalance, oxidative stress, mitochondrial dysfunction and BBB disruption have been identified to be important pathological events that are involved at acute stages following BINT 3 4 5 6 7 8 9 10 11 12 13 14 15 21 22 23 . However, the long-term effects on various pathological markers and associated cognitive deficits are currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reports have shown loss of neuronal populations, while also showing an increase in astrogliosis 3 4 5 6 7 8 9 10 11 12 . The limited number of magnetic resonance imaging studies combined with histopathological data have shown the vulnerability of oligodendrocytes and endothelial cells following BINT 13 14 15 . In conjunction with molecular changes, behavioral abnormalities such as memory impairment and anxiety have been widely demonstrated in acute pre-clinical studies 11 16 17 .…”
mentioning
confidence: 99%
“…TBI has a powerful dysregulating effect on the endocrine system 19 and particularly TBI secondary to blast-wave exposure. 20 It is believed that overactivity of the "hypothalamic-pituitary-adrenal" axis, through acute or chronic stress, disrupts the hormonal interaction (including gonadal and thyroid axes) between this region of the brain and the adrenal gland. This increases the secretion of cortisol and norepinephrine, leading to insomnia or sleep disruption.…”
Section: Endocrine Dysfunctionmentioning
confidence: 99%
“…As such, TBI survivors can present with deficiencies in one or more hormones, including corticotropins, growth hormones, thyrotropins, and gonadotropins ( 20 ). The variation of hormones disrupted could be based on the type (blast, diffuse, penetrating), mechanics (direction/force of impact) or dynamics (single, repetitive) of the injury, as well as pre-existing conditions (genetic predisposition) ( 23 , 24 , 25 , 26 , 27 , 28 ). Recent longitudinal studies support the idea that a severe injury is more likely to result in chronic endocrine dysfunction, as opposed to a mild injury; however, endocrine dysfunction manifests across the brain injury severity spectrum ( 15 ).…”
Section: Introductionmentioning
confidence: 99%